Training and establishment survival - William Collier; Francis Green; David Wilkinson (University of Kent, Department of Economics, 2002)
We investigate the relationship between training and the likelihood of commercial survival over a 7-year period, using a survey of British establishments. We find that in establishments of 200 or more employees, increased training of those in Professional, Sales, and Clerical and Secretarial occupations is associated with a greater chance of survival. In smaller establishments of less than 200 employees, increased training for Operatives and Assembly workers, Personal and Protective Service workers, and Craft and Technical workers is associated with better chances of survival. We interpret these findings as suggesting that training for these groups generated above-normal returns.
Keywords: J24; J51; L21; 330; Training; survival; economic performance; Betriebliches Bildungsmanagement; Unternehmensentwicklung; Schätzung; Großbritannien; Korrelation